2007
DOI: 10.1016/j.jcrysgro.2007.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Co-precipitation of silica and alkaline-earth carbonates using TEOS as silica source

Abstract: We explore the use of tetraethoxysilane (TEOS) as a silica source for the formation of carbonate-silica composite materials known as 'biomorphs'. The basic hydrolysis of TEOS furnishes silica in a controllable fashion, allowing a significantly higher reproducibility of the obtained silica-barium and silica-strontium carbonate co-precipitates compared to commercial water glass silica used so far. We further discuss the influence of ethanol used as a co-solvent on the morphologies of biomorphs, which are examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 17 publications
7
66
0
Order By: Relevance
“…In the absence of any further additive, silica-barium carbonate self-assembly results in this case typically in racemates of regularly wound helical filaments (Fig. 2), curvilinear sheets as well as thicker croissant-like braids (''worms''), as documented in detail in earlier work [18,23,24].…”
Section: Control Experimentssupporting
confidence: 64%
See 2 more Smart Citations
“…In the absence of any further additive, silica-barium carbonate self-assembly results in this case typically in racemates of regularly wound helical filaments (Fig. 2), curvilinear sheets as well as thicker croissant-like braids (''worms''), as documented in detail in earlier work [18,23,24].…”
Section: Control Experimentssupporting
confidence: 64%
“…Previous studies on the Si/Ba ratio in silica biomorphs led to a diverse range of values, depending on the type of morphology as well as on the respective position within an aggregate. For instance, Si/Ba percentages of 15-29% were reported for biomorph helices, while 6-35% was found for worms [18,37]. Coralline CaCO 3 biomorphs were claimed to contain 35-40% Si relative to Ca 26 .…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Strictly speaking, Voinescu et al [22,23] reported the formation of silica-calcium carbonate biomorphs showing ''coralline'' self-assembled shapes, these synthetic aggregates being built by aragonite nano-crystals and an amorphous silica matrix. Nevertheless, the thermal conditions for precipitation were sharply different from those used to obtain the usual silica biomorphs [12,14], since the authors operated far from the room temperature (80 1C).…”
Section: Introductionmentioning
confidence: 99%
“…EDX data (lower panels in Figure 4 bd) confirm the presence of appreciable amounts of silica, with Si/Ba atomic ratios of skin-bearing biomorphs ranging from about 0.15 to 0.4, in good agreement with values reported previously for syntheses run under similar conditions. [21,22] Coherent results were obtained when determining the average Si content of bulk samples prepared by homogenizing a great deal of aggregates. On the other hand, highmagnification FESEM micrographs and AFM images of biomorphs grown for 8 h or less reveal a bare carbonate core instead of a smooth silica surface ( Figure 5).…”
mentioning
confidence: 99%